QUANTITATIVE EVALUATION OF REVENUE ALLOCATION TO STATES AND LOCAL GOVERNMENTS IN NIGERIA (1999-2008) - Olubusoye Olusanya Elisa; Oyedotun Temitope D. Timothy (European Scientific Journal, ESJ, 2012)
As a follow-up to our last paper on Spatio-temporal information system analysis of revenue allocation in Nigeria, this article presents a quantitative evaluation of the statutory, value added tax and excess crude oil revenue allocation to states and the local governments in Nigeria between May 1999 – December 2008. A comparative and cluster analyses were conducted among the 36 states and 774 local government areas of the country to examine the state and local governments with similar (dissimilar) features in terms of revenue allocation, and we found that overall, a good number of states and local governments in Nigeria have similar trends in revenue allocation.